2022
DOI: 10.1177/10600280221075362
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen-Associated Hypokalemia and Metabolic Acidosis: Systematic Literature Review

Abstract: Objective: Ibuprofen is a widely used nonsteroidal anti-inflammatory drug, which has been occasionally associated with hypokalemia and metabolic acidosis. The objective of this report is to analyze the literature on this issue and to address the underlying pathophysiology. Data Sources: Excerpta Medica, the National Library of Medicine, and Web of Science were searched from inception to July 16, 2021. Study Selection and Data Extraction: Papers reporting individually documented humans on ibuprofen with hypokal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 101 publications
(154 reference statements)
1
5
0
Order By: Relevance
“… 8 A recent review discussing ibuprofen-induced hypokalemia and metabolic acidosis showed that in the case of acute ingestion, an altered state of consciousness is a major feature, even in patients with intake of a normal dosage. 9 A further argument for ibuprofen as the causative agent in the present case is that visual impairment has been previously described in cases of ibuprofen overdose. 10 Furthermore, visually-evoked potentials may show prolonged latencies and reduced amplitudes in patients with ibuprofen overdose.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“… 8 A recent review discussing ibuprofen-induced hypokalemia and metabolic acidosis showed that in the case of acute ingestion, an altered state of consciousness is a major feature, even in patients with intake of a normal dosage. 9 A further argument for ibuprofen as the causative agent in the present case is that visual impairment has been previously described in cases of ibuprofen overdose. 10 Furthermore, visually-evoked potentials may show prolonged latencies and reduced amplitudes in patients with ibuprofen overdose.…”
Section: Discussionsupporting
confidence: 52%
“… 12 Disregarding these severe side effects, discontinuation of ibuprofen usually results in complete resolution of the conditions described above. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ibuprofen has been previously linked to hypokalemia and RTA. [10][11][12][13][14][15] A recent systematic review 12 found 50 reported cases of patients with profound hypokalemia and/ or acidosis after ibuprofen use and most cases had evidence of impaired urinary acidification or renal potassium wasting. Notably, this review found 3 lethal cases and that hypokalemia and acidemia were also seen at doses generally regarded as safe (<40 mg/kg of body weight).…”
Section: Discussionmentioning
confidence: 99%
“…Acquired distal renal tubular acidosis (RTA) is associated with the use of NSAIDs, characterized by impaired distal acidification of urine due to a reduction in net hydrogen ion secretion in the distal nephron. The primary mechanism by which NSAIDs like ibuprofen induce metabolic acidosis is linked to their impact on renal function, specifically affecting renal tubular processes [ 111 ]. It has been observed that ibuprofen, a commonly utilized NSAID, is associated with the development of hypokalemia and metabolic acidosis.…”
Section: The Nexus Of Viral Infection Metabolic Acidosis and Nsaid-in...mentioning
confidence: 99%